I contributi di J. N. Brønsted e di T. M. Lowry alla definizione di acidi e basi - Calascibetta, Franco (Chimica nella Scuola, 2024)
The two physical chemists Johannes Nicolaus Brønsted (1879-1947) and Thomas Martin Lowry (1874-1936)1are usually jointly credited with the definition of acids and bases in terms of acceptors and donors of H+ ions. Each on his behalf, in a completely independent manner, in the same year, 1923, they in fact published two articles from which the aforementioned definition originates. We aim to analyze the contents of these articles to illustrate the different paths taken by the two scientists to arrive at this result.